Vpliv občutljivosti motivacijskih sistemov BIS in BAS na izvajanje rehabilitacijskih nalog po možganski kapi - Milavec, Maja (Psihološka obzorja (Ljubljana), 2011)
Stroke rehabilitation programs are often too short and not intensive enough, possibly due to a lack of patient motivation. This study examined whether the patient's mood, task success and psychophysiological responses are affected bythe sensitivity of two motivational systems: the Behavioral Activation System (BAS) and the Behavioral Inhibition System (BIS). 22 subacute stroke patients participated in the study. They performed an easier and harder version of a motor rehabilition task as well as the Stroop task. The sensitivities of the two motivational systems were measured using the BIS/BAS scale. Additionally, psychophysiological measurements (heart rate, skin conductance, respiration and skin temperature) were taken and the Self-Assessment Manikin was used to measure self-reported valence and arousal. Results showed that valence and arousal are not significantly correlated with BIS/BAS subscales during the rehabilitation task. A negative correlation between valence and the BAS subscales was found in the Stroop task. Results also confirmed the initial hypothesis that the BAS would be correlated with task performance during the rehabilitation task while the BIS would be negatively correlated with task performance during the Stroop task. Only partial confirmation was found for the hypothesis that tasks that includea reward would affect heart rate in subjects with a sensitive BAS while tasks without a reward would affect skin conductance in subjects with a sensitive BIS. In both versions of the rehabilitation task, which includes a reward, the BAS reward subscale was negatively correlated with mean skin temperature. In the harder rehabilitation task, the BAS reward responsiveness subscale was positively correlated with mean heart rate. In the Stroop task, which has no reward, the BIS scale was positively correlated with mean heart rate. The BAS subscale was also negatively correlated with the RMSSD measure of heart rate variability. The results of the study suggest that rehabilitation task designers should take the subject's BIS/BAS motivational systems into account when designing the task rewards and difficulty.
Keywords: motivacija; motivation; rehabilitacija; rehabilitation; vocational rehabilitation; motivacijski sistem umika; behavioral inhibition system; nagrajevalni motivacijski sistem; behavioral activation system; cerebrovascular accidents; možganska kap; rehabilitacijske naloge; stroke; rehabilitation tasks; psihofiziologija; psychophysiology; Lestvica BIS/BAS; BIS/BAS scales; Stroopov barvno-besedni test; Lestvica SAM; Stroop colour word test; Self-assessment manikin (SAM)